المسئولية المدنية لهيئات الرقابة الشرعية في المصارف الإسلامية- دراسة في ضوء القانون الإماراتي - محمد سادات, محمد (revue mofakir; No 14 (2017): مجلـــة المفكــر, 2018)
Islamic‬‬ ‫‪banks‬‬ ‫‪represent‬‬ ‫‪a‬‬ ‫‪supporting‬‬ ‫‪Islamic‬‬ ‫‪Economics‬‬ ‫‪tools‬‬ ‫‪in‬‬ ‫‪practice,‬‬ ‫‪and‬‬ ‫‪is‬‬ ‫‪considered‬‬ ‫‪Islamic‬‬ ‫‪banking‬‬ ‫‪services‬‬ ‫‪in‬‬ ‫‪investment‬‬ ‫‪banking‬‬ ‫‪activities‬‬ ‫‪brick‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪edifice‬‬ ‫‪of‬‬ ‫‪Islamic‬‬ ‫‪finance,‬‬ ‫‪and‬‬ ‫‪an‬‬ ‫‪important‬‬ ‫‪tool‬‬ ‫‪of‬‬ ‫‪the‬‬ ‫‪effectiveness‬‬ ‫‪of‬‬ ‫‪tools‬‬ ‫‪of‬‬ ‫‪applications‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪Muslim‬‬ ‫‪community.‬‬If the states take the necessary controls to control and requirements on the work of these banks to ascertain the extent of its compatibility with the Central Bank's policies, the same Islamic banks, put some kind of control, seeking through it to make sure of the extent of the discipline of banking transactions with the provisions of Islamic law, which is called Shari'a Supervisory. The importance of research in that the subject is important, because to follow the banks of the Shari'a was preparing the way to escape from the effects of the global financial crisis that occurred in 2008, also show the importance of control of legitimacy through the important role they play within the Islamic bank, which show the extent of the financial institution to the provisions of commitment Islamic law in all financial and banking transactions, which are of great importance for Islamic banks to more than one reason. If the work of the Shari'a Supervisory Board is one of the important work on the agenda of the Islamic bank system, arises the question of whether issued a kind of dereliction of Shari'a Supervisory Board, including the consequent mixing of clients Riba funds, or the loss of the rights of the parties to banking transactions, whether bank or depositors, which raises civil liability of a body, and arise with questions about the nature of the liability and the terms of the establishment, and whether the body damage included, or are there other hand, guaranteed? All this in addition to many other questions required by the study.